The Role of Glycemic Control and Variability in Diabetic Retinopathy - Chatziralli, Irini P. (Diabetes Ther, 2017)
Diabetic retinopathy (DR) is a common microvascular complication of diabetes mellitus (DM) and is considered the leading cause of visual impairment in working-aged adults worldwide. The duration of DM and hyperglycemia have been associated with DR, although the exact role in the pathogenesis of DR and diabetic macular edema remains controversial. As a result, a reasonable question arising is whether control of blood glucose levels may alter the course of DR. Studies have shown that glycemic control remains an important factor for the presence and progression of DR. HbA1c seems to be an indicator which cannot demonstrate exactly the degree of glycemic control, while sudden variations of blood glucose may play an important role in DR; therefore, glycemic variability may be useful to predict DM complications, such as DR.